The Haemostatic Balance)) - Astrup, Tage (Thrombosis and Haemostasis, 1958)
The roles played by the blood clotting system and by fibrinolysis in the haemostatic balance are discussed. The significance of the tissue thromboplastin and the tissue activator of plasminogen for local haemostasis is emphasized, and their relation to anticoagulant therapy considered. Problems specific for coronary thrombosis, cerebral thrombosis and cerebral haemorrhage have been mentioned.